Power Production Waste. (1st October 2018) - Ye, Junpei; Wang, Siqi; Zhang, Panyue; Nabi, Mohammad; Wang, Hongjie
Abstract : This paper reviewed the research literatures published in 2017 about power production waste generated from fuel and nuclear power plants. The treatment, reuse, management and disposal of power production waste were mainly considered. The wastes from different power plants mainly include fly ash, flue gas desulfurization gypsum and waste selective catalytic reduction catalyst, and so on. The monitoring, management, treatment and disposal of power production waste were also reviewed.